Beyond the scenes of crime: the ghost of Tenório Jr. amidst the dissonances and disputes in the historiography of Brazilian jazz (1964-1976) (Orfeu, 2021)
We analyze the aesthetic-ideological disputes that were forged from the formation of a new place for instrumental music, between the 1960s and 70s – context of profound changes in the parameters of production and music consumption. We used the trajectory of pianist Tenório Jr. as the guiding thread of the analysis. Quite evoked, the argument that correlates the tragedy of the musician to the market position of Brazilian instrumental music has had significant acceptance, reproducing in the bibliography on the subject. Because of this, we revisit the history of this historical character (complex plot involving memory, music and dictatorship) and examine the extent to which the facts ratify or refute the thesis that the “devaluation” of the instrumental is related and consummated in the face of what happened to it. With the intersection of sources and historiographical discussion, we show in the work evidence that there are limits to the use of the musician’s life as a symbol of the supposed “death” of the instrumental.
Keywords: musical memory; sambajazz; brazilian jazz/instrumental; dictatorship; Latin America